Caracterização de bactéria fixadora de nitrogênio em Lupinus albescens - Stroschein, Marcos Roberto Dobler (2007)
The objective of this work was to characterize promising isolated rhizobium of L. albescens in the nitrogen biological fixation. Two hundred and four isolates were obtained from three species of lupine (L. albescens, L. lanatos e Lupinus sp.). Thirty-eight isolates chosen randomly were characterized through their phenotype and submitted to an authenticity test done in the greenhouse. In order to select symbiotic strains that synthesizes leghaemoglobin. The promising isolates were identified by their phenotypic characteristics by comparing twenty-one strains of rhizobium. The physiological characteristics of the promising isolated were determined and evaluated about the growing capacity in different temperatures, NaCl concentrations and pH, and a molecular characterization by polymerase chain reaction (PCR) using the primer BOX. An experiment, in the greenhouse, was made to determine the symbiosis efficiency by the total nitrogen, and the dried mass in the aerial part and in the roots, and the number of nodules. The phenotypic characterization of the thirty-eight isolated enabled the development of 11 groups with distinct characteristics. The UFSM L1.3 strain developed nodules and leghaemoglobin when associated to L. Albescens and was identified in the genus Bradyrhizobium. The UFSM L1.3 strain presented growing in the temperature from 28 to 32°C, in a NaCl concentration of 0,1% and in a pH from 4,0 to 8,0. The standard of polymorphism generated by the primer BOX-PCR enabled to distinguish the UFSM L1.3 isolated from the others. The symbiosis efficiency of the UFSM L1.3 isolated was of 94,2% when compared to the without nitrogen.